2015
DOI: 10.1111/bju.13031
|View full text |Cite
|
Sign up to set email alerts
|

Transperineal biopsy prostate cancer detection in first biopsy and repeat biopsy after negative transrectal ultrasound‐guided biopsy: the Victorian Transperineal Biopsy Collaboration experience

Abstract: ConclusionsTPB is an alternative approach to TRUS biopsy of the prostate, offering a high rate of detection of clinically significant prostate cancer. It provides excellent sampling of the anterior region of the prostate, which is often undersampled using the TRUS approach, and should be considered as an option for all men in whom a prostate biopsy is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 53 publications
(99 reference statements)
2
23
0
4
Order By: Relevance
“…Transrectal ultrasound-guided prostate biopsy neglects prostate cancer located in the anterior fibromuscular stroma, whereas the TPUSPB does not. 16 In our study, a significant proportion of positive prostatic cores were found in the anterior fibromuscular stroma among patients in the TPUSPB group. Moreover, some patients with prior negative findings in TRUSPB were diagnosed with prostate cancer in the anterior fibromuscular stroma based on the results of TPUSPB.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Transrectal ultrasound-guided prostate biopsy neglects prostate cancer located in the anterior fibromuscular stroma, whereas the TPUSPB does not. 16 In our study, a significant proportion of positive prostatic cores were found in the anterior fibromuscular stroma among patients in the TPUSPB group. Moreover, some patients with prior negative findings in TRUSPB were diagnosed with prostate cancer in the anterior fibromuscular stroma based on the results of TPUSPB.…”
Section: Discussionsupporting
confidence: 48%
“…First, a consistent number of cores was biopsied in all patients in the TPUSPB group, irrespective of prostate size. To improve the rate of prostate cancer detection, some experts have advocated for the use of different numbers of prostate biopsies, based on prostate size 16 -more biopsies should be taken in patients with larger prostates. Second, TPUSPB required more time than TRUSPB.…”
Section: Discussionmentioning
confidence: 99%
“…Rectal cleansing with povidine‐iodine enemas has shown some benefit but the technique does not negate the need for antibiotic prophylaxis . With limited sustainable options for escalating TRUS biopsy prophylaxis, our institution has been increasingly utilising transperineal prostate biopsy, which we have shown to have a near‐zero sepsis rate , as well as offering a high rate rate of detection of clinically significant prostate cancer . With more limited resources it may be appropriate to reserve transperineal prostate biopsies to those patients at higher risk of harbouring resistant organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, various methods permit the results of the mpMRI to guide subsequent prostate biopsy; however, the most efficient is probably the MRI‐TRUS fusion method. The biopsy approach can also be transperineal, which is accepted as safer when possible sepsis‐related complications of the transrectal approach are considered . Aside from how the needle is placed in the prostate, whether perineal or transrectal, MRI plays a major role in identifying the target lesion(s) and guiding the needle path.…”
Section: Mpmri‐transrectal Ultrasound Fusion Biopsiesmentioning
confidence: 99%